Analisis Frekuensi Denyut Jantung Istirahat Pelari dan Bukan Pelari di Kota Padang - Ihsan Otriami; Mefri Yanni; Mohamad Reza; Cimi Ilmiawati (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Running is increasingly popular in Indonesia as a recreational and competitive sport. Training volume per week is known to be associated with the cardiorespiratory fitness of runners. A straightforward method of assessing fitness is by measuring the resting heart rate (RHR). Objective. This study aimed to analyze the RHR and its runners, recreational runners, and non-runners in the city of Padang, West Sumatera. Methods. This cross-sectional study recruited 51 subjects by purposive sampling (elite runners n= 16, recreational runners n=15, and non-runners n=20). RHR (beat per minute [bpm]) was measured using electrocardiography, while exercise volume perweek (km) was obtained using an electronic questionnaire (Google form). Data were analyzed using the Spearman correlation test, Mann-Whitney U test, and One-way ANOVA/Kruskal-Wallis. Results. The results of this study indicated that the RHR of elite runners was lower than recreational runners and non-runners (55.0; 65.2; 73.4 bpm, respectively; p = 0.001). The correlation between training volume per week and RHR was not statistically significant in elite runners (Spearman r=-0.31; p=0.25), but statistically significant in recreational runners (Spearman r=-0.73; p=0.002). Conclusion. It can be concluded that elite runners have the best cardiorespiratory fitness, followed by recreational runners and non-runners. There is a correlation between weekly training volume and RHR in recreational runners, but not in elite runners.